2011
DOI: 10.1111/j.1747-7379.2011.00848.x
|View full text |Cite
|
Sign up to set email alerts
|

Partner Selection and Divorce in Ethnic Minorities: Distinguishing between Two Types of Ethnic Homogamous Marriages

Abstract: This article compares divorce risks according to marriage type. The common dichotomy between ethnic homogamous and ethnic heterogamous marriages is further elaborated by differentiating a third marriage type; ethnic homogamous marriages between individuals from an ethnic minority group and a partner from the country of origin. Based on the analysis of data concerning the Turkish and Moroccan minorities in Belgium, it has been confirmed that the divorce risk associated with these marriages is higher than that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 34 publications
(73 reference statements)
2
22
0
3
Order By: Relevance
“…The rates of transnational marriages among children of Turkish immigrants are higher than among children of Moroccan immigrants. Moreover, other studies have shown that Moroccan migrants experience significantly higher risks of divorce in transnational marriages compared to Turkish migrants (Eeckhaut et al ., ). These differences might in part be due to the more tight‐knit networks in the Turkish community together with different levels of religiosity and values (Crul and Doomernik, ).…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…The rates of transnational marriages among children of Turkish immigrants are higher than among children of Moroccan immigrants. Moreover, other studies have shown that Moroccan migrants experience significantly higher risks of divorce in transnational marriages compared to Turkish migrants (Eeckhaut et al ., ). These differences might in part be due to the more tight‐knit networks in the Turkish community together with different levels of religiosity and values (Crul and Doomernik, ).…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…There has been much less research on the effects of religious or ethnic exogamy on marital stability in a European context. To our knowledge only a few studies exist, such as Finnäs (1997) on linguistic exogamy in Finland, Kalmijn et al (2005) on religious and nationality exogamy in the Netherlands, and Eeckhout et al (2011) on ethnic exogamy in Belgium. This apparent lack of knowledge calls for much more research in European contexts, which are often characterized by high immigration rates and poor societal integration of large immigrant groups (Rotte and Stein 2002;Zimmermann 2005).…”
Section: Introductionmentioning
confidence: 98%
“…For example, Lesthaeghe and Surkyn (1995) identify a considerable degree of heterogeneity and heteropraxis among Turkish and Moroccan immigrants in Belgium and argue that marriage migration is an important source of such intra-community cultural variation. Eeckhaut et al (2011) study the same immigrant groups and find that marriage migration, as hypothesized, is associated with increased divorce risk. They also argue that, due to a higher degree of social support, divorce risks should be lower in more closely knit immigrant communities.…”
Section: Previous Research On Divorce Among Immigrantsmentioning
confidence: 99%
“…That is, for a non-negligible share of immigrants the decision to leave the country of origin was motivated by the intention to marry a person living in Sweden. Marrying a partner from the country of origin is not uncommon among immigrants in Sweden and elsewhere in Europe (Charsley 2005;Eeckhaut et al 2011;van Kerckem et al 2013;Obućina 2014). To illustrate, the most common reason for granting residence permits in Sweden is family reunification: in the period 2002-2006 three out of four of these permits were issued to "newly formed marriages" (Parusel 2009).…”
Section: Marriage Formation Among Immigrantsmentioning
confidence: 99%